Energy transfer cooperation between ligands and EuIII ions in molecular europium complexes for vapoluminescence sensing (reversible on/off emission switching) and hybrid white LED/plant-growth applications. Issue 42 (18th October 2021) - Rajendran, Marikumar; Devi, Rachna; Mund, Sibani; Singh, Kasturi; Vaidyanathan, Sivakumar
Abstract : In a europium complex, two ancillary ligands were designed to provide complete energy transfer to the Eu(iii ) ion. Abstract : In a europium complex, two ancillary ligands were designed to provide complete energy transfer to the Eu(iii ) ion. Both ligands were successfully synthesized and utilized for europium complexation (Eu(TTA)3 -phen-fl-mCF3, Eu(TTA)3 -phen-fl-pCH3, Eu(DBM)3 -phen-fl-mCF3, and Eu(DBM)3 -phen-fl-pCH3 ). The ligands display deep blue emission, whereas their corresponding europium complexes exhibit pure red emission ( 5 D0 → 7 F2, electric dipole transition). Photophysical and electrochemical analyses were carried out in detail. The theoretical and experimental studies confirmed that complete energy transfer occurred from the ligands to the Eu(iii ) ion. The color purity was also calculated for the complexes, among them, the Eu(TTA)3 -phen-fl-mCF3 complex showed the highest color purity (98.36%). The pure red emissive Eu-complexes were integrated with near UV light emitting diodes (LEDs) to fabricate a red LED. The Eu(TTA)3 -phen-fl-mCF3 complex was blended with yellow dye conjugated on a blue LED to produce a white LED, the white LED showed warm white light with CIE ( x = 0.336; y = 0.377) and lower CCT (5360 K) and superior CRI (81) values. The hybrid deep-red-LED was fabricated to study a plant cultivation application, the EL spectrum entirely covered the phytochrome Pr absorption spectrum. Also, a film of Eu-complex revealed on–off–on luminescence performance under an atmosphere of acid–base. The combination of Eu(iii ) complex + NaSrGd(MoO4 )3 :Sm 3+ orange red phosphor based deep-red LED showed prominent coverage of the absorption spectrum of phytochrome Pr.